(untitled) (Philological Studies, 2019)
The relations between an author and a reader as the most significant version of pair I and Another in the art world are considered in the article. The author and the reader are an equal in rights partners during dialogical attitudes in the literary text. The purpose of the research is studying how does process of understanding of the literary text depend on a particular situation and the text. The study of literary texts from the point of view of the reflection of various forms of the I / another relation is argued here. The meeting of the author with the reader is a meeting of two consciousnesses. This is a dialogical event relating to sphere of spiritual culture. A context of understanding can be defined as a complex of the points of view, system of ideals, value representation, valuable orientations of the subject. The authors allocated five types of the contexts of understanding in the text (the author and the reader and their «others»). Contexts cooperate according to author’s intention as they are united with the important and the most essential information. As the result of the study the authors comes to the conclusion which could be worded as follows. The interaction of a set of unique «I-contexts» («author’s» and «reader’s» being) creates a certain idea of the literary text, expands an outlook of subjects and can change their point of view. Thus, the understanding is possible at collision of different value contexts: a context of the author, a context of the reader and a context of the hero. The meeting of different contexts, outlooks is a dialogue. It is conducted in space of the text and goes back to space of culture. «The dialogue of cultures» («questioning-answering» in M.M. Bakhtin’s terminology) is a «life» of the literary text in «big time» as the actualization of its idea.